On the Effect of Sex on Prefrontal and Cerebellar Neurometabolites in Healthy Adults: An MRS Study - Endres, Dominique; Tebartz van Elst, Ludger; Feige, Bernd; Backenecker, Stephan; Nickel, Kathrin; Bubl, Anna; Lange, Thomas; Mader, Irina; Maier, Simon; Perlov, Evgeniy (Frontiers in Human Neuroscience, 2016)
In neuropsychiatric research, the aspects of sex have received increasing attention over the past decade. With regard to the neurometabolic differences in the prefrontal cortex and the cerebellum of both men and women, we performed a magnetic resonance spectroscopic (MRS) study of a large group of healthy subjects. For neurometabolic measurements, we used single-voxel proton MRS. The voxels of interest were placed in the pregenual anterior cingulate cortex (pACC) and the left cerebellar hemisphere. Absolute quantification of creatine (Cre), total choline (t-Cho), glutamate and glutamine (Glx), N-acetylaspartate, and myo-inositol (mI) was performed. Thirty-three automatically matched ACCs and 31 cerebellar male–female pairs were statistically analyzed. We found no significant neurometabolic differences in the pACC region (Wilks’ lambda: p=0.657). In the left cerebellar region, we detected significant variations between the male and female groups (p=0.001). Specifically, we detected significantly higher Cre (p=0.005) and t-Cho (p=0.000) levels in men. Additionally, males tended to have higher Glx and mI concentrations. This is the first study to report neurometabolic sex differences in the cerebellum. The effects of sexual hormones might have influenced our findings. Our data indicates the importance of adjusting for the confounding effects of sex in MRS studies.